2007
DOI: 10.1007/s11661-007-9303-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Treatment and Scandium Addition on the Electrochemical Polarization Behavior of Al-Zn-Mg-Cu-Zr Alloy

Abstract: In this study, the electrochemical polarization behaviors of Al-Zn-Mg-Cu-Zr (7010) alloy in three different heat treatments, namely, underaged, peak-aged, and overaged, were examined in 3.5 wt pct NaCl solution. Experimental results show that the cathodic current increases marginally in the order of underaged < peak-aged < overaged alloys, which has been attributed to an increase in copper content of the precipitates in general and the grain boundary precipitates (GBPs) in particular. The change in the precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 24 publications
(47 reference statements)
2
13
0
Order By: Relevance
“…Then the R t of the three zones decreases rapidly, and the difference between the three zones decreases as the reaction time increases. When the Al–Zn–Mg alloy is immersed in a neutral aerated solution, the following anodic reactions may occur: normalMnormalgnormalZn2 falsenormal(normalinormaln.25emnormalGnormalP.25emnormalznormalonormalnnormalenormals,ηnormalanormalnnormaldη)normalMg2goodbreakprefixnormal++2normalZn2goodbreakprefixnormal++6e, normalAnormall.25em(normalinormaln.25emnormalsnormalonormallnormalinormald.25emnormalsnormalonormallnormalunormaltnormalinormalonormaln)goodbreaknormal→normalAl3goodbreakprefixnormal+goodbreaknormal+3e,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the R t of the three zones decreases rapidly, and the difference between the three zones decreases as the reaction time increases. When the Al–Zn–Mg alloy is immersed in a neutral aerated solution, the following anodic reactions may occur: normalMnormalgnormalZn2 falsenormal(normalinormaln.25emnormalGnormalP.25emnormalznormalonormalnnormalenormals,ηnormalanormalnnormaldη)normalMg2goodbreakprefixnormal++2normalZn2goodbreakprefixnormal++6e, normalAnormall.25em(normalinormaln.25emnormalsnormalonormallnormalinormald.25emnormalsnormalonormallnormalunormaltnormalinormalonormaln)goodbreaknormal→normalAl3goodbreakprefixnormal+goodbreaknormal+3e,…”
Section: Resultsmentioning
confidence: 99%
“…Then the R t of the three zones decreases rapidly, and the difference between the three zones decreases as the reaction time increases. When the Al-Zn-Mg alloy is immersed in a neutral aerated solution, the following anodic reactions may occur [1,21,22] :…”
Section: Electrochemical Testmentioning
confidence: 99%
“…With regard to the SCC resistance, Braun [56] and Wang et al [57] reported no benefi cial effect of Sc addition to Al-Mg alloys. In contrast, Kannan and Raja [58] and Yi-Lei et al [59] reported the benefi cial effect of Sc addition towards the SCC resistance in Al-Zn-Mg-Cu alloy. Kannan and Raja [8,58] showed that the 7010 alloy containing 0.25 wt% Sc exhibited a high SCC resistance even in the peak-aged condition.…”
Section: Compositionmentioning
confidence: 95%
“…In contrast, Kannan and Raja [58] and Yi-Lei et al [59] reported the benefi cial effect of Sc addition towards the SCC resistance in Al-Zn-Mg-Cu alloy. Kannan and Raja [8,58] showed that the 7010 alloy containing 0.25 wt% Sc exhibited a high SCC resistance even in the peak-aged condition. They attributed the improvement in the SCC resistance to the sharp reduction in the recrystallized grains and change in the morphology of the grain boundary precipitates (i.e.…”
Section: Compositionmentioning
confidence: 95%
“…Examination of these curves has indicated that the cathodic currents are almost independent of the applied potential. Because of the heterogeneities present in the material, the cathodic kinetics is accelerated and drives the E corr towards more nobler potentials and this leads to pinning of E corr with pitting potential (E pit ) 13) . The cathodic currents under different heat treatments marginally increased in the order; peak aged< retrogressed and re-aged.…”
Section: Potentiodynamic Polarizationmentioning
confidence: 99%